Increasing the psychosocial focus in child developmental assessments: a qualitative study - Sarah de Voss; Philip Wilson; Sofie Saxild; Gritt Overbeck (BMC Pediatrics, 2023)
Abstract Background Previous studies have indicated a need for increased psychosocial focus on children and their families to improve children’s wellbeing and mental health. Child developmental assessments could be a place to implement changes to achieve this. A standardised record might be helpful to clinicians trying to increase psychosocial focus. The aim of this study is to investigate clinical barriers and facilitators when introducing standardised child records with increased focus on psychosocial wellbeing and mental health into child developmental assessments. Methods This is a qualitative study based on 12 semi-structured interviews with four midwives and nine doctors who carry out child developmental assessments in general practice. Data is analysed in the framework of Normalisation Process Theory. Results General practice-based clinicians were positive towards increasing the psychosocial focus in child developmental assessments. The main barriers when clinicians used the standardised child records were: feeling forced to ask certain questions, in turn making the conversation rigid; leaving less room for parents to bring up other issues; making clinicians feel awkward when addressing problems that they cannot solve; the need for extended consultation time; and medico-legal concerns when registering findings. The experience of positive aspects when using the standardised child records facilitated continuous use of the records. Positive aspects included having a standardised approach to recording important findings, thereby uncovering psychosocial problems that could potentially be overlooked. Additionally, structured observation of parent–child interaction and gaining a new vocabulary to describe the findings were valued by clinicians. Balancing a standardised approach with clinicians’ ability to steer the consultation and explore topics in depth while preserving the potential for patients to bring up other issues became an important theme. Conclusion Clinicians need to be well-equipped to handle psychosocial problems through coping strategies, referral options and communication techniques in the psychosocial domain. The parent–child-interaction assessment might expose potentially dysfunctional parenting behaviours and could improve communication between health professionals. Implementing standardised child development records with an increased psychosocial focus is feasible but improvements could optimise the use of the records. Parental views on an increased psychosocial focus during child developmental assessments should be investigated prior to further implementation. Trial registration Trial registry number for the FamilieTrivsel (Family Wellbeing) trial: NCT04129359.